THE EMPIRICAL RELATIONSHIP BETWEEN THE STAKEHOLDER INVOLVEMENTS, PROJECT MANAGER SKILLS, TOP MANAGEMENT STRATEGY AND PROJECT SCOPE MANAGEMENT: A STUDY ON GOVERNMENT PROJECTS IN THE SULTANATE OF OMAN - Qais Hashil Salim Al-Rubaiei, Faizatul Akmar Abdul Nifa, Suria Musa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to examine the relationship between the stakeholder's involvement, project manager skills, top management strategy and project scope management in the funded government project in the Sultanate of Oman. A mapping of this relationship has been issued in previous paper to highlight the importance of these variables and effect on the scope management. A statistical tool which is SPSS was used to analyze the data collected. The findings indicated that there are positive and significant relationship between the stakeholder's involvement, project manager skills, top management strategy and project scope management. Moreover, these variables can be further tested to evaluate their effect on government projects. The findings also confirmed that stakeholder's involvement, project manager skills, top management strategy has positive effect on the project scope management. Finally, the study suggested numbers of others influencing factors for future study on the project management practices of government projects.